Savings and Loans SYSTEM ON KOPERASI SERBA USAHA "TUNAS JAYA" USING VISUAL BASIC 6.0 - Sulistyaningsih Sulistyaningsih (Jurnal Sistem Informasi, 2007)
Scholarly Writing with this place the author attempted to help the Multipurpose Cooperative Enterprises "TUNAS JAYA" by making the design Savings and Loan System as a replacement system manual. Research methods used were interviews and Method Method Library. With this application program in Visual Basic 6.0 Multipurpose Cooperative Enterprises "TUNAS JAYA", action employment data accuracy can be further increased, the accumulation of archives and documents can be avoided and the creation of reports document can be easily processed. While the proposed suggestion of considering the importance of data files used in important, it must be noted in the data treatment is to Back Up.